Monetary Policy Crisis Management as a Threat to Economic Order - Andreas Freytag; Gunther Schnabl (Credit and Capital Markets – Kredit und Kapital, 2017)
The paper analyses the effects of monetary policy crisis management of the European Central Bank on the economic order of Germany. It is argued that in post-war Europe the German social market economy as designed by Eucken (1952) and Müller-Armack (1966) has been a core element of growth, welfare, social cohesion and political stability in Germany and Europe as a whole. It is shown that the monetary policy rescue measures of the European Central Bank have undermined the constitutive principles of the German social market economy, which has considerably contributed to the erosion of (productivity) growth and welfare in Germany and Europe. As the outcome is crumbling social cohesion and growing political instability, a timely exit from ultra-expansionary monetary policy is postulated. – – Geldpolitisches Krisenmanagement als Gefahr für die Wirtschaftsordnung Der Artikel untersucht die Effekte des geldpolitischen Krisenmanagements der Europäischen Zentralbank auf die Wirtschaftsordnung. Es wird argumentiert, dass im Europa der Nachkriegsjahre die deutsche Marktwirtschaft (Soziale Marktwirtschaft), wie sie von Eucken (1952) und Müller-Armack (1966) entwickelt worden war, ein Kernelement für Wachstum, Wohlstand, sozialen Zusammenhalt und politische Stabilität in Deutschland und Gesamteuropa war. Es wird gezeigt, dass die geldpolitischen Rettungsmaßnahmen der Europäischen Zentralbank die konstituierenden Prinzipien der Sozialen Marktwirtschaft untergraben haben, was maßgeblich zu sinkendem (Produktivitäts-)Wachstum in Deutschland und Europa beigetragen hat. Da dies zunehmend den sozialen Zusammenhalt in Europa gefährdet sowie eine steigende politische Instabilität nach sich zieht, wird ein baldiges Ende der ultralockeren Geldpolitik gefordert.
Keywords: B20; E14; B25; 330; Crisis Management; Europe; Alfred Müller-Armack; Economic Order; Social Market Economy; Soziale Marktwirtschaft; Germany; Walter Eucken; Monetary Policy